2022
DOI: 10.1108/ijsms-06-2021-0123
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting users’ stickiness of fitness apps: an empirical study based on the S-O-R perspective

Abstract: PurposeDespite fitness applications (apps) are increasingly downloaded by smartphone users in recent years, the usage behavior after initial adoption often lasts for a short period of time for most users. The purpose of this paper is to explore factors affecting stickiness of fitness app and then indicate how to retain existing users.Design/methodology/approachA research model was developed based on stimulus–organism–response (S-O-R) model. Using the data collected from 231 fitness app users through an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Therefore, the observed variables can be in principle interchanged without altering the meaning of a concept. For example, the behavioral concept stickiness precedes measures such as “I plan to keep using … in the future” and “I intend to continue using … than use any alternative means” (Teng and Bao, 2022, Appendix), not vice versa. In contrast to the reflective measurement, in the case of a causal-formative measurement, the observed variables are assumed to be causes of the concept, i.e.…”
Section: Three Criteria To Categorize Behavioral and Formed Conceptsmentioning
confidence: 99%
“…Therefore, the observed variables can be in principle interchanged without altering the meaning of a concept. For example, the behavioral concept stickiness precedes measures such as “I plan to keep using … in the future” and “I intend to continue using … than use any alternative means” (Teng and Bao, 2022, Appendix), not vice versa. In contrast to the reflective measurement, in the case of a causal-formative measurement, the observed variables are assumed to be causes of the concept, i.e.…”
Section: Three Criteria To Categorize Behavioral and Formed Conceptsmentioning
confidence: 99%
“…Although this model was developed in environmental psychology, many researchers have used this framework to examine individuals’ behavioral responses in different research areas such as store environment, online learning, online social networks, and online video watching ( Vieira, 2013 ; Zhai et al, 2020 ; Masrom et al, 2021 ; Wang and Yue, 2022 ). In the fields of online health and fitness, recent studies also utilizing the S-O-R theory have demonstrated the effect of platform characteristics as environmental stimuli on individuals’ internal reactions and consequent behavioral responses related to fitness applications and community ( Elsotouhy et al, 2022 ; Teng and Bao, 2022 ; Zhou et al, 2022 ). However, researchers have paid little attention to applying this framework in short fitness videos.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…Previous research on MFA has explored the design [16], evaluation [17,18,84,85], and user adoption [19] of MFA. In addition, several studies have discussed continuity in the use of MFA [20][21][22][23]. Chiu et al [21] integrated expectation-confirmation theory with the investment model to analyze the continuous use of MFA.…”
Section: Introductionmentioning
confidence: 99%